PENYULUHAN HUKUM BAHAYA NARKOBA BAGI GENERASI MUDA PADA MASYARAKAT KEBONAGUNG KECAMATAN PLOSO JOMBANG - Arkisman, Arkisman; Ningsih, Dwi Wachidiyah; Nasichin, Moh (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
The abuse of narcotics and illegal drugs among the younger generation is currently increasing, and deviant behavior among the younger generation can threaten the survival of this nation in the future. Narcotics Law No. 35 of 2009 regulates investigation, prosecution and preliminary examination in narcotics criminal court sessions, more precisely in §§ 73-103. In each line of drug cases, the investigation process is the most important process in eradicating drug dependence. Article 35 of Law Number 2009 concerning Narcotics also contains Article 54 which regulates rehabilitation. Article 54, which reads: "Drug addicts and victims of drug dependence must attend medical rehabilitation and social rehabilitation. Medical rehabilitation of addicts can be carried out in hospitals designated by the Minister of Health, namely hospitals organized by the state or city government. Through medical rehabilitation in addition to ongoing treatment or treatment, the city government can carry out the process of healing drug addicts by religious and traditional means.